Pengaruh Permainan Number Tube terhadap Kemampuan Berfikir Simbolis Anak Usia Tk 4-5 Tahun di TK Negeri Menara Laut Kelurahan Leato Utara Kota Gorontalo - Selpi Selpi; Nunung Suryana Jamin; Sulastya Ningsih (Inovasi Pendidikan dan Anak Usia Dini, 2026)
The problem in this study is to determine what is the effect of the number tube game on the symbolic thinking ability of 4-5 year olds. The aim is to reveal whether there is a number tube game on the symbolic thinking ability of 4-5 year old children at Menara Laut State Kindergarten, Leato Utara Village, Dumbo Raya District, Gorontalo City. The type of research used is a quantitative experiment. The subject of this study is how to determine the effect of the number tube game. The method used in this study is the observation and documentation method. Based on the results of the observation, it was found that the symbolic thinking ability in recognizing numbers in children has not developed optimally. Although teachers have tried to introduce numbers, most children still have difficulty in naming, ordering, and writing numbers. Children also need teacher assistance to understand numbers 1-10 and distinguish between certain numbers such as 6 and 9. Therefore, a more effective and fun learning strategy is needed to help children understand the concept of numbers symbolically. In this case, it can be concluded that improvements through the application of the number tube game. This game was chosen because it is simple, easy to use, and in accordance with the characteristics of early childhood. Through a play-while-learning approach, children are expected to be able to recognize numbers more easily.